How Voters Decide : Information Processing in Election Campaigns. - Lau, Richard R. (Cambridge studies in public opinion and political psychology., 2006)
This book proposes a new framework for studying voter decision making. An innovative experimental methodology is presented for getting 'inside the heads' of citizens as they confront the overwhelming rush of information during modern presidential election campaigns. Four broad types of decision strategies are described.